Shaping violences: state formation, symbolic violence and the link between public and private interests in Brazil - Ferreira, Marcos Alan; Holanda Maschietto, Roberta [UNESP] (Taylor & Francis, 2025)
This article examines the relationship between state formation, symbolic violence, and the blurring of public and private interests in Brazil. Drawing on a variety of sources–including academic literature, government reports, and media accounts–we use a historical approach to analyse how these factors have contributed to violence in Brazil, focusing on the case of the Northeast region. We argue that both symbolic violence and the problematisation regarding the separation between public and private interests have been overlooked in statebuilding literature. The blurring of public and private interests, grounded in symbolic violence (through the naturalisation of racism and aporophobia), contributes to sustained historical patterns of violence in Brazil. These patterns were introduced during the colonial period and have persisted to this day.
Keywords: extermination groups; Northeast of Brazil; state formation; Statebuilding; symbolic violence